Prevention and rehabilitation of muscle hypotonicity of vertebrogenic origin during preparation for the main competitions of the season - Ilyin A.B.; Cherkasov A.D.; Ivkov A.N.; Morozov V.I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop a methodology for testing the muscular system of athletes and special regular physical exercises as a method of preventing muscle hypotonicity in the biomechanical parts of the muscular topography of athletes, built into the structure of training sessions. Methods and structure of the study. To identify muscle hypotonicity, muscle testing methods (according to L.F. Vasilyeva), used in kinesiology, and methods of functional tests for lateroflexion were used. The study of the state of the muscular system was carried out with the participation of athletes specializing in basketball, swimming, water polo, and kickboxing. To correct muscle condition, special physical exercises were developed and used. Results and conclusions. Long-term observations have revealed an important pattern, namely: spastic conditions in skeletal muscles occur the next day after consuming sugar, rice and flour products in increased quantities, especially against the background of high physical activity during the period of centralized training. The developed and tested system of physical exercises allows not only to eliminate impaired muscle tone, but also to prevent the entire complex of dystrophic disorders in the muscular system of the spine.